A10 SIRT2 inhibition achieves neuroprotection by decreasing sterol biosynthesis. (16th November 2010) - Taylor, D; Pallos, J; Lambert, E; Amore, A; Parker, A; Moffitt, H; Smith, D; Runne, H; Gokce, O; Kuhn, A; Xiang, Z; Maxwell, M; et al.
Abstract : Background: Huntington's disease (HD) has a complex pathogenesis, including protein aggregation and the dysregulation of neuronal transcription and metabolism. Aims: We assessed whether inhibition of sirtuin 2 (SIRT2) could achieve neuroprotection in models of HD and defined the mechanism(s) by which this modality acts at the cellular level. Methods/techniques: Genetic or pharmacologic inhibition of SIRT2 was assessed for neuroprotective effects in cellular and invertebrate models of HD, and the molecular mechanism of the SIRT2 inhibition was defined in rat striatal neurons. Results/outcome: SIRT2 inhibition resulted in neuroprotection in fly, worm and primary striatal cell models of HD. Microarray gene expression profiling further revealed correlated expression changes including significant downregulation of RNAs responsible for sterol biosynthesis. Whereas mutant huntingtin fragments increased sterols in neuronal cells, SIRT2 inhibition reduced sterol levels via decreased nuclear trafficking of SREBP-2. Importantly, manipulation of sterol biosynthesis at the transcriptional level mimicked SIRT2 inhibition, demonstrating that the metabolic effects of SIRT2 inhibition are sufficient to diminish mutant huntingtin toxicity. Conclusions: These data identify SIRT2 inhibition as a promising avenue for HD therapy and elucidate an important and novel mechanism of SIRT2–inhibitor mediated neuroprotection. Furthermore, the ascertainment of SIRT2's role in regulating cellular metabolism demonstrates a central function shared with other sirtuin proteins.